Engaging with Culture in Teaching of English as a Foreign Language in Finland: A Teacher Perspective - Aitio, Pinja (My University, 2022)
This study focuses on English teachers’ engagement with culture in their teaching and in textbooks. Their views are compared to the Finnish national curricula, which contain numerous cultural aims for foreign language teaching and learning. Culture’s role within foreign language teaching has been extensively studied since it factors in the learners’ communicative and intercultural competences. However, Finnish foreign language teachers’ voice is still unheard in reflecting their subjective views of culture teaching and its connection to the cultural content in textbooks. The aim of this study is to explore English teachers’ conceptions of culture in various contexts. The data were collected via semi-structured interviews that were conducted on six English teachers in Finland. The data analysis was done following principles for qualitative data analysis. The results suggest that the teachers’ conception of culture is broad, and they highlight the importance of intercultural competence in their teaching. Textbooks are a significant resource for culture teaching, which is why teachers often rely on them despite often finding stereotyping representations of cultures in them. The teachers expressed being unfamiliar with the cultural aims for foreign language education in the national curricula, but their personal aims corresponded positively with what the national curricula state. The results of this study underline the importance of cultural awareness being a part of lifelong learning, as teachers need to be constantly retrained to be able to offer culturally responsible education for the students to improve their intercultural competence. Teachers’ views related to culture in foreign language teaching need to be further studied in a wider perspective to improve the foothold culture has in foreign language education.
Keywords: culture teaching, English as a foreign language